2018
DOI: 10.2478/sjph-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of patients in need of palliative care in slovenian general practice

Abstract: BackgroundTo help general practitioners (GPs) in early identification of patients with palliative care (PC) needs, this pilot study aimed to determine the potential of the combined original surprise question (SQ1) (‘Would I be surprised if this patient died within the next 12 months?’) and the second surprise question (SQ2) (‘Would I be surprised if this patient was still alive after 12 months?’). We hypothesized that answering these SQs would trigger them to make a multidimensional care plan.Methods26 Sloveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Case vignette studies showed that general practitioners are willing to use the Double Surprise Question. 17 , 18 In an explorative study, the prognostic accuracy of the Double Surprise Question for patients aged ⩾75 years in general practice was examined. It was shown that the Double Surprise Question is able to discriminate between patients with different life expectancies and palliative care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Case vignette studies showed that general practitioners are willing to use the Double Surprise Question. 17 , 18 In an explorative study, the prognostic accuracy of the Double Surprise Question for patients aged ⩾75 years in general practice was examined. It was shown that the Double Surprise Question is able to discriminate between patients with different life expectancies and palliative care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the NP demonstrated higher accuracy for predicting whether patients would still be alive after 12 months compared to PCP. Our results suggest the use of “12-SQ2”: “Would I be surprised if this patient is still alive after twelve months?” ( 45 ) for physicians with a background in neurology or a combination of the original 12-SQ and the 12-SQ2, which has been piloted in a sample of general practitioners ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified many facilitators to improve the organization of palliative care. Similar facilitators regarding the organization of palliative care and useful tools exist in different countries (van Riet Paap, et al, 2014;Mistry, et al, 2015;Klok, et al, 2018, WHO, 2014):…”
Section: Facilitatorsmentioning
confidence: 98%